p53-Mediated Cell Cycle Arrest and Apoptosis Induced by Shikonin via a Caspase-9-Dependent Mechanism in Human Malignant Melanoma A375-S2 Cells - Zhen Wu; Lijun Wu; Linhao Li; Shin-ichi Tashiro; Satoshi Onodera; Takashi Ikejima (Elsevier, 2004)
Natural products regulate cell growth in response to oncogene activation that induces cell cycle arrest and apoptosis in tumor cell lines. We investigated the mechanisms of caspase activation in human malignant melanoma, A375-S2 cells, by the natural product shikonin, which was isolated from the plant Lithospermum erythrorhizon SIEB. et ZUCC. Shikonin inhibited cell growth in a time- and dose-dependent manner, which might be mediated through up-regulation of p53 and down-regulation of cyclin-dependent protein kinase 4. Caspase activation was detected in shikonin-induced cell apoptosis, which involved in a post-mitochondrial caspase-9-dependent pathway. Decreased Bcl-2 protein levels and increased Bax protein levels were positively correlated with elevated expression of p53 protein. Apoptosis-inducing factor, another apoptotic protein of mitochondria, partially contributed to shikonin-induced release of cytochrome c. Taken together, shikonin-induced DNA damage activates p53 and caspase-9 pathways. Keywords:: shikonin, cell cycle arrest, apoptosis, caspase, p53